Effectiveness of mechanical vs. chemomechanical methods in removing intracanal calcium hydroxide medication: a randomised trial - Amir, Nehal; Noor, Nouman (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the mechanical and chemomechanical methods for removing calcium hydroxide medication from the root canal system. Method: The triple-blind, randomised clinical trial was conducted at the Department of Operative Dentistry and Endodontics, School of Dentistry, Shaheed Zulfiqar Ali Bhutto Medical University, Islamabad, Pakistan, from December 16, 2022, to June 15, 2023, and comprised patients having necrotic teeth and chronic apical pathosis. They were randomised into groups A and B. On the initial visit, after access opening and chemomechanical preparation, calcium hydroxide paste was placed as an intracanal medication in both groups. the patients were recalled after two weeks. In Group A, calcium hydroxide was removed from the canals using a rotary master apical file, while in Group B, an endoactivator was used to sonically agitate the endodontic irrigant. Verification of placement was done by using a periapical radiograph. Data was analysed using SPSS 26. Results: Of the 98 individuals assessed initially, 60(61.22%) were included; 34(57%) females and 26(43%) males with age ranging from 19 to 57 years. There were 27(45%) incisors, 22(36.7%) premolars and 11(18.3%) canines. There were 30(50%) patients in each of the 2 groups. The intergroup difference was not statistically significant (p=0.43). Tooth arch did not significantly correlate with the removal method (p=0.79). Conclusion: Both methods were found to be equally effective in removing water-based calcium hydroxide medication from the endodontic system. Clinical Trial Number: NCT05744661. Key Words: Calcium hydroxide, Dental pulp necrosis, Microbiota, Periapical periodontitis, Root canal therapy.